S’accorder. La régulation sociale dans les justices locales de l’Ouest parisien au xviiie siècle - Pierre-Benoît Roumagnou (Criminocorpus)
Did the populations around Paris in the 18th century entrust the settlement of their disputes to the justice system or did they settle them alone, before a notary? In other words, what was the relationship between justice as a virtue and the courts of first instance as an administration?